Temporal trend of congenital syphilis in Palmas, Tocantins: analysis by inflection points, 2008 to 2018 - Gomes Duvale, Ariane; Pinto de Rezende Nobre da Silva, Nayá; Caroline Tocantins Alvim, Mariana; Patrícia Lino Pereira Franchi, Eliane; Mackartney de Souza Marinho, Ana; Dias Monteiro, Lorena (Journal of Health Care, 2021)
NTRODUCTION: Syphilis is a worldwide public health problem. In Palmas, capital of Tocantins, the detection rate of congenital syphilis (CS) was higher than the average for the state and Brazil in 2018. Despite this, this is a subject that has not been studied in the town. OBJECTIVE: to describe the temporal trend of CS in the capital of TO, through the analysis of inflection points in the period from 2008 to 2018. METHODS: A time series study based on epidemiological data from the Department of Informatics of the Unified Health System. The temporal trend analysis included Poisson regression models by inflection points (Joinpoint). RESULTS: 451 cases of SC were recorded, whose detection rate showed a significant increase in the period 2010-2018 (APC = 11.8 - 95% CI 3.9 to 20.3). In the total period, there was a significant decrease in late SC (APC = -8.1 - 95% CI -13.3 to -2.6), SC of mothers aged 30 to 39 years (APC = -6.0 - 95% CI -10.4 to -1.4) and SC with appropriate treatment (APC = -23.1 - 95% CI -32.5 to -9.7). In the same period, there was a significant increase in SC in mothers aged 15 to 19 years (APC = 10.4 - 95% CI 4.9 to 16.2), with 10 to 12 years of study (APC = 3.2 - 95% CI 0.2 to 6.3) and with inadequate treatment (APC = 5.5 - 95% CI 0.2 to 11.1). In the period from 2011 to 2018, there was a significant drop in SC with an untreated partner (APC = -5.8 - 95% CI -10.7 to -0.5). CONCLUSION: For better indicators, it is necessary to improve prenatal care, including, essentially, partners in the treatment of the disease, in addition to the promotion of sex education in schools for the adolescent population.